AB0904 Prevalence of different immune-mediated inflammatory diseases in patients with spondyloarthropaties. Aquiles study. (23rd January 2014) - García-Vicuña, R.; Zarco, P.; Rodríguez de la Serna, A.; Peirό, E.; Collantes, E.; Cea-Calvo, L.; Nadal, J.A.; Vanaclocha, F.; Marín-Jiménez, I.; González, C.
Abstract : Background: AQUILES is a 2-year follow-up observational prospective study in patients with spondyloarthritis (SpA), inflammatory bowel disease [IBD] or psoriasis, to assess: 1) the coexistence of immune-mediated inflammatory diseases (IMID); 2) the prevalence of comorbidities and 3) the incidence of new clinical manifestations of IMID over a 2-year follow-up period Objectives: To describe the baseline characteristics and the prevalence of concomitant IMIDs in the population with diagnosis of SpA recruited in Rheumatology offices Methods: From March 2008 to December 2010, patients with known or newly diagnosed SpA, IBD or psoriasis were recruited from Rheumatology, IBD and Dermatology offices (15 centers). For Rheumatologists, inclusion criteria were age ≥18 years-old and previous or new diagnosis of SpA. Clinical data were collected through direct interview and patient's clinical record review following a protocol agreed by the 3 specialties Results: In Rheumatology offices, 563 patients were recruited (mean age: 48.5 years-old [SD: 12.7]; 62.5% males, 37.5% females; mean disease duration 7 years [IQR: 2-14]). A history of familial SpA was present in 19.2%, and 7.5% had newly diagnosed SpA. The diagnoses at baseline were: ankylosing spondylitis (AS) (52.9%), psoriatic arthritis (PsA) (25.2%), undifferentiated SpA (7.3%), enteropathic arthritis (2.3%), and others (12.3%). BASDAI activity index was 3.4 (SD: 2.6). The proportion of SpA patients with IBD at baseline was 5.0% (Crohn disease: 3.0%, ulcerative colitis: 1.1%, indeterminate colitis: 0.9%). The proportion was similar in men and women (4.4% vs. 5.9%, p=NS), in patients with familial vs. sporadic SpA (1.9% vs. 6.4%, p=0.064), or new vs. known SpA (5.0% vs. 4.8%, p=NS). Excluding those with enteropathic arthritis, the proportion with IBD was 2.7% (3.0% in AS, 1.4% in PsA, 2.4% in undifferentiated SpA, p=NS). The proportion of patients with psoriasis was 27.5% (4.5% excluding PsA; 4.4% in AS, 95.8% in PsA, 4.9% in undifferentiated SpA; p<0.05 for PsA vs. the others), was higher in women (33.3% vs. 25.3% in men, p=0.044) and similar in familial vs. sporadic (21.3% vs. 30.0%, p=0.075) or new vs. known disease (21.4% vs. 28.0%, p=NS). Finally, the prevalence of uveitis was 13.3% (19.6% in AS, 0.7% in PsA, 12.2% in undifferentiated SpA; p<0.05 for PsA compared to the others), and was similar in men and women (14.4% vs. 12.3%, p=NS) and in new vs. known disease (9.5% vs. 13.6%, p=NS), but higher in those with familial disease (21.3% vs. 10.7% in sporadic SpA, p=0.004) Conclusions: In patients with SpA recruited in Rheumatology offices for the AQUILES study in Spain, the proportion with other IMIDs was similar to that described in the literature, and higher than the known prevalence in general population of Spain. We did not observe relevant differences between those with newly diagnosed and previously known SpA Disclosure of Interest: R. García-Vicuña: None Declared, P. Zarco: None Declared, A. Rodríguez de la Serna: None Declared, E. Peirό: None Declared, E. Collantes: None Declared, L. Cea-Calvo Employee of: Merck Sharp & Dohme, J. Nadal Employee of: Merck Sharp & Dohme, F. Vanaclocha: None Declared, I. Marín-Jiménez: None Declared, C. González: None Declared